Staying or Leaving? Examining the Role of Work–Life Balance and Competence in Shaping Turnover Intention in the Hotel Industry - Nathalie Aurelia Simangunsong; Dewi Khrisna Sawitri (Jurnal Riset Akuntansi, 2026)
This study aims to analyze the effect of work-life balance and competence on the turnover intention of permanent employees at Midscale Hospitality Setting. The background of this study is based on the high employee turnover rate, which reached 23% in 2025, exceeding the hospitality industry standard. This research employs a quantitative approach using a saturated sampling technique involving 64 respondents. Data were collected through questionnaires, interviews, observations, and literature review, and analyzed using Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach. The results indicate that all variable indicators meet the validity and reliability criteria. Simultaneously, work-life balance and competence explain 33.4% of the variance in turnover intention. Hypothesis testing reveals that work-life balance has a negative and significant effect on turnover intention, indicating that better balance between work and personal life reduces employees’ intention to leave the organization. In addition, competence also has a negative and significant effect on turnover intention, with a stronger influence compared to work-life balance. These findings suggest that improving employee competence through training, as well as implementing policies that support work-life balance, can be effective strategies to reduce turnover rates. This study provides practical contributions to human resource management in the hospitality industry, particularly in enhancing employee loyalty and workforce stability.